Kinematical analysis of five different kicks in taekwondo - Falcó, C.; Estevan, I.; Vieten, M. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to identify those foot techniques in taekwondo to the head with the highest potential for success in competition. We compared five of the most frequently used kicks, the round kick, front leg axe kick, clench axe kick, jump spin back kick and jump spin hook kick. Since the right timing and fast movements vastly determine success, we looked at the reaction time, execution time and total response time. Eight high level athletes participated in the study. Three Casio HD cameras operated on 300 Hz were used to record kinematics parameters. A Hybrid II Crash Dummy head (H2D) and neck were instrumented. The one-way ANOVA showed that there were no differences in reaction time while there were differences in the execution time and, as a consequence, in the total time (p < .01) as well.